The Doctor–Patient Relationship and Information-Seeking Behavior: Four Orientations to Cancer Communication. Issue 2 (April 2018) - Adamson, Matthew; Choi, Kelsey; Notaro, Stephen; Cotoc, Crina
Background: In cancer communication, patients and physicians often understand a patient's experience and situation differently. This can negatively impact health outcomes and the physician–patient relationship. Aim: To explore how cancer patients' interpretations of the physician's role as information giver affect the communication relationship with the physician and their information-seeking behavior regarding different aspects of their cancer care. Design: Participants completed a semistructured qualitative interview addressing their treatment experience and communication with their physician. Interviews were coded and analyzed using inductive thematic analysis. Setting/Participants: Ten patients with cancer treated at a regional cancer center in central Illinois participated in the study. Cancer stages I to IV and 4 cancer types were represented. Results: Participants' orientations to the relationship with their physician (and their information-seeking behavior) were classified into 4 general categories: (1) "questioners" have a general mistrust toward their physicians and the information doctors are giving; (2) "the undecided" focuses on physician "fit, " often requiring time to step away in order to make decisions and process information; (3) "cross-checkers" are concerned with content of their treatment protocol, often double-checking the treatment plan; and (4) "the experience-oriented" feel a gap between their experience and their physician's experience (and perspective), often seeking information from other survivors. All categories described a perceived lack of adequate exchange of information and the need to seek information outside of the physician–patient relationship to compensate. Conclusion: Participants exhibited different information-seeking behaviors based on how they interpreted the role of their physician as information giver. This affected what kind of information they sought and how they understood the information received, which in turn affected understanding of their broader experience and care.